Vaping product access and use among 14–17‐year‐olds in New South Wales: a cross‐sectional study. (26th September 2022) - Watts, Christina; Egger, Sam; Dessaix, Anita; Brooks, Alecia; Jenkinson, Emily; Grogan, Paul; Freeman, Becky
Abstract: Objectives : We assessed access to vaping products and types of products used and the factors associated with vaping and smoking among young people in the state of New South Wales (NSW), Australia. Methods : A cross‐sectional survey was conducted with a sample of 721 young people aged 14 to 17 years from NSW recruited through online panels. Poisson regression with robust variance was used to estimate relative risks of ever‐vaping and ever‐smoking. Results : Almost one‐third of the sample (32%, n=233) reported being an ever‐vaper, of which more than half (54%) had never smoked prior to starting vaping. Ever‐vaping was independently associated with age and being Aboriginal or Torres Strait Islander, and ever‐smoking was independently associated with being male. Ever‐smokers were seven times more likely to be ever‐vapers than those who had never smoked, and ever‐vapers were 18 times more likely to be ever‐smokers than those who had never vaped. Among ever‐vapers who reported which type of device they were using, 86% reported the use of disposable products. "Flavourings and taste" was rated as the most important characteristic of vapes. More than half of ever‐vapers reported getting the last vape they used from their friends (55%, n=130). More than half of ever‐vapers had used a vape that they knew contained nicotine (53%, n=123). Conclusions : Vaping was the strongest risk factor for smoking, and vice versa, suggesting there is not a straightforward, unidirectional relationship between vaping and smoking in young people. Young people appear to be readily accessing nicotine vaping products, which are often disposable and flavoured, through both social and commercial channels. Implications for public health : Stronger enforcement of federal and state policies designed to protect young people from vaping products is urgently needed.